The Effect of Differences Dam's Bodymaterials on Factories of Elasticity and Strength on Safety Factor (Journal of Hama University, 2019)
This search aims to know the effects of differences of earth Dam's Bodymaterials specifically on elasticity and strength factors,Using Geo-studio software on analyzing the slop stability of Maharadeh Dam, the factor of safety was determined considering two conditions:The case of maximum level of water and the case of minimum level of water using numerical programs that depends on the finite elements method, by changing each factor within its possible range with the stability of the other factories still fixed. The results show that the safety factor depends mostly on angle of internal friction. Finally, some suggestions have been given.